2017
DOI: 10.1111/ppc.12217
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness and parenting distress among parents of children with disabilities: A literature review

Abstract: The results of this first review on the topic provide preliminary support for the efficacy of MBIs for supporting parents of children with disabilities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 32 publications
2
29
2
Order By: Relevance
“…Items were rated using a 4-point Likert scale ranging from 0 ("Did not apply to me at all") to 3 ("Applied to me very much, or most of the time") and were summed to yield a single total score between 0 and 42 with higher scores indicating greater levels of distress. The DASS has been used as a measure of parent psychological distress in both intervention and non-intervention studies that included parents of autistic individuals (Conner and White 2014;Lunsky et al 2015;Rayan and Ahmad 2018). In a previous study (Lunsky et al 2017), a 14-item psychological distress score demonstrated excellent internal consistency (Cronbach's α = 0.94).…”
Section: Dassmentioning
confidence: 99%
“…Items were rated using a 4-point Likert scale ranging from 0 ("Did not apply to me at all") to 3 ("Applied to me very much, or most of the time") and were summed to yield a single total score between 0 and 42 with higher scores indicating greater levels of distress. The DASS has been used as a measure of parent psychological distress in both intervention and non-intervention studies that included parents of autistic individuals (Conner and White 2014;Lunsky et al 2015;Rayan and Ahmad 2018). In a previous study (Lunsky et al 2017), a 14-item psychological distress score demonstrated excellent internal consistency (Cronbach's α = 0.94).…”
Section: Dassmentioning
confidence: 99%
“…Furthermore, mindfulness-based interventions for parents of children with chronic issues (attention deficit hyperactivity disorder, developmental delays, autism) have been shown to be effective for lessening parental stress and mental health problems. Improvements in parentchild relationships and improved youth behavior management have also been found [33].…”
Section: Mindfulness-based Interventionsmentioning
confidence: 96%
“…Da Paz and Wallander () narratively reviewed varied forms of psychological interventions on their efficacy in augmenting the mental health of parents with children living with ASD, but inconclusive evidence was found. Four reviews examined the efficacy of mindfulness‐based interventions on the mental health of parents of children with developmental disabilities (Cachia et al, ; Keenan‐Mount et al, ; Ó Donnchadha, ; Rayan & Ahmad, ). The narrative reviews found that mindfulness‐based interventions were effective in relieving parental stress.…”
Section: Introductionmentioning
confidence: 99%
“…Reviews that aim to evaluate the efficacy of psychological interventions in improving the stress, depression as well as anxiety of parents with children and adolescents with developmental disabilities are warranted as previous reviews are outdated, synthesized narratively or focused on a specific type of psychological intervention (Cachia, Anderson, & Moore, 2016;Da Paz & Wallander, 2017;Hastings & Beck, 2004;Keenan-Mount, Albrecht, & Waters, 2016;Ó Donnchadha, 2018;Rayan & Ahmad, 2018;Singer, Ethridge, & Aldana, 2007). Hastings and Beck (2004) evaluated the efficacy of stress management interventions in relieving stress faced by parents of children with learning disabilities using a narrative summary.…”
Section: Introductionmentioning
confidence: 99%